Changing Police Personal Safety Training Using Scenario-Based-Training: A Critical Analysis of the ‘Dilemmas of Practice’ Impacting Change - Cushion, Christopher (Frontiers in Education, 2022)
This paper outlines an analysis of using Scenario-Based-Training (SBT) to change officer Personal Safety Training (PST) based on existing research evidence and reflections from supporting a National Police Agency attempting to change PST practice. SBT is interrogated in light of its underlying assumptions and situated within the ambiguities, tensions and compromises inherent within police training cultures. Using Windschitl’s framework of conceptual, pedagogical, cultural, and political dilemmas this paper analyses the forces impacting using SBT to change PST. An alternative agenda for change is presented to develop skilled officers and trainers equipped with innovative pedagogies to ‘re-culture’ PST.